The Mediterranean fishery management: A call for shifting the current paradigm from duplication to synergy. (September 2021) - Cardinale, Massimiliano; Colloca, Francesco; Bonanno, Angelo; Scarcella, Giuseppe; Arneri, Enrico; Jadaud, Angélique; Saraux, Claire; Aronica, Salvatore; Genovese, Simona; Barra, Marco; Basilone, Gualtiero; Angelini, Silvia; et al.
Abstract: Independence of science and best available science are fundamental pillars of the UN-FAO code of conduct for responsible fisheries and are also applied to the European Union (EU) Common Fishery Policy (CFP), with the overarching objective being the sustainable exploitation of the fisheries resources. CFP is developed by DG MARE, the department of the European Commission responsible for EU policy on maritime affairs and fisheries, which has the Scientific, Technical and Economic Committee for Fisheries (STECF) as consultant body. In the Mediterranean and Black Sea, the General Fisheries Commission for the Mediterranean (FAO-GFCM), with its own Scientific Advisory Committee on Fisheries (GFCM-SAC), plays a critical role in fisheries governance, having the authority to adopt binding recommendations for fisheries conservation and management. During the last years, advice on the status of the main stocks in the Mediterranean and Black Sea has been provided both by GFCM-SAC and EU-STECF, often without a clear coordination and a lack of shared rules and practices. This has led in the past to: i) duplications of the advice on the status of the stocks thus adding confusion in the management process and, ii) a continuous managers' interference in the scientific process by DG MARE officials hindering its transparency and independence. Thus, it is imperative that this stalemate is rapidly resolved and that the free role of science in Mediterranean fisheries assessment and management is urgently restored to assure the sustainable exploitation of Mediterranean marine resources in the future. Highlights: Advice on the status of the main stocks in the Mediterranean and Black Sea is provided both by GFCM-SAC and EU-STECF. Duplication of the advice on the status of Mediterranean and Black Sea stocks creates confusion in the management process. Continuous interference in the scientific process by DG MARE officials has hindered its transparency and independence. It is imperative that this stalemate is resolved and that the free role of science in Mediterranean fisheries is restored.